HUBUNGAN BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN BAGIAN ADMINISTRASI DI AUTO 2000-CAO JAKARTA - Anggraini, Nenny; Simamora, Engelina Lawita; Lumbantoruan, Rutman (Fundamental Management Journal, 2016)
Research conducted at the AUTO 2000 - CAO Jakarta to determine the relationship of organizational culture and motivation on employee performance of Administration. The purpose of this study was to determine the relationship of organizational culture and employee performance, motivation and performance of employee relations, cultural relations organization and motivation on the performance of employees in the Administrative AUTO 2000-CAO Jakarta. This research is descriptive-correlational by as many as 30 employees, and the data were analyzed using Spearman Rank analysis and correlation. The results of this study indicate that (1) there is a significant relationship between organizational culture and employee performance of Administration AUTO 2000-CAO Jakarta. It ditujukkan with the obtained t (2.309) is greater than t table (2.048). (2) there is a significant relationship between motivation and performance of employees of the Administration AUTO 2000-CAO Jakarta. It ditujukkan with the obtained t (4.105) is greater than t table (2.048). (3) there is a significant relationship between organizational culture and motivation simultaneously with employee performance of Administration AUTO 2000-CAO Jakarta. It ditujukkan with Fhitung obtained (4.771) greater than F table (3,354). Based on the results, it can be concluded that the organizational culture in the company is very strong and must be protected and maintained. Organizations need to be more enthusiastic in enhancing innovation to improve the quality of work. Work motivation has also been very strong in the company. Bosses and employees motivate each other to each other and thus creating an increase in the employee morale. While in terms of performance also has been very good and still be maintained by the briefing or coffe morning in order to create good communication between employees.Key word : organizational culture, motivation, employee performance